Neuroprotective Effects of Fingolimod in a Cellular Model of Optic Neuritis - Amritha A. Candadai (MDPI AG, 2021)
Visual dysfunction resulting from optic neuritis (ON) is one of the most common clinical manifestations of multiple sclerosis (MS), characterized by loss of retinal ganglion cells, thinning of the nerve fiber layer, and inflammation to the optic nerve. Current treatments available for ON or MS are only partially effective, specifically target the inflammatory phase, and have limited effects on long-term disability. Fingolimod (FTY) is an FDA-approved immunomodulatory agent for MS therapy. The objective of the current study was to evaluate the neuroprotective properties of FTY in the cellular model of ON-associated neuronal damage. R28 retinal neuronal cell damage was induced through treatment with tumor necrosis factor-α (TNFα). In our cell viability analysis, FTY treatment showed significantly reduced TNFα-induced neuronal death. Treatment with FTY attenuated the TNFα-induced changes in cell survival and cell stress signaling molecules. Furthermore, immunofluorescence studies performed using various markers indicated that FTY treatment protects the R28 cells against the TNFα-induced neurodegenerative changes by suppressing reactive oxygen species generation and promoting the expression of neuronal markers. In conclusion, our study suggests neuroprotective effects of FTY in an in vitro model of optic neuritis.